Baby-box schemes in England: parent and practitioner experiences, and recommendations - Ball, Helen L. (BMC Pediatr, 2020)
BACKGROUND: Programmes offering carboard baby boxes to parents in England began in some NHS Trusts in 2016. This study aimed to examine the strengths and weaknesses of English baby-box schemes as experienced by healthcare providers and parents. METHODS: An independent mixed-methods evaluation was conducted via telephone interviews and online surveys with healthcare providers and parents in all 7/9 NHS regions of England where baby-box schemes were established 2016–2019. Participants responded to requests circulated electronically by NHS Research & Design Departments, and infant health organisations in England. The objectives were to identify how parents and healthcare providers understood and experienced baby-box schemes implemented in England to date, and to produce recommendations for organisations considering involvement in future schemes. RESULTS: Baby-box schemes changed over time, and were complex to run and monitor. Both parents and practitioners were misinformed about their purpose and origins. Partnerships with a commercial box-provider reduced the investment needed to run a baby-box scheme, and offered potential benefits to staff regarding engagement with families via online education and face-to-face contact around handover of boxes, but carried unforeseen costs. Of particular concern was the box-provider’s access to parent personal details being promoted by NHS staff and parents’ lack of awareness; the hidden costs incurred by NHS facilities of running a box-scheme; and the costs incurred by parents in accessing their ‘free’ box. Sixteen recommendations are proposed for healthcare providers and organisations considering commercial - health-provider baby-box partnerships in future. CONCLUSIONS: Many assumptions exist about the origins and purpose of baby-boxes; this misinformation needs correcting, especially as it relates to infant death reduction and safe infant sleep. Baby-box schemes take multiple forms from those motivated by social welfare to those motivated by commercial profit. The English experience of partnership schemes between healthcare facilities and commercial box-providers reveals some success stories, along with multiple points of ambiguity, unanticipated difficulty, and concerns for infant safety.